The Dynamic Effect of Oil Rent on Industrial Value Added: a SVAR Approach - Fakhri Issaoui; Talel Boufateh; Ghassen El Montasser (Economics and Econometrics Research Institute (EERI), 2013)
This paper studies the dynamic effect of oil rents on industrial added value in a sample of countries with different levels of development. Using a SVAR model, we tested the effect of a real shock and a nominal shock on the variables of the model. The main obtained results are three. First, we confirmed that the Dutch disease (DD) problem is a short-term phenomenon that takes place each time there is a shock on oil rents. Second, the ephemeral nature of the phenomenon confirms the neoclassical assumption stating that the effect of nominal shocks on real variables is only short term. Third, the effect of long-term real shock on oil rents is positive for all countries which score interdependence between industry on the one hand and oil rents on the other.
Keywords: E37; Q32; Q34; Q38; Q43; 330; Dutch disease; Oil rents; Industrial added value; SVAR; Tunisia